The comparative analysis of the welfare attitude in accordance with the dual status of taxpayer and welfare recipient by using data linkage: IJPDS (2017) Issue 1, Vol 1:126, Proceedings of the IPDLN Conference (August 2016) - Oh, Miae; Choi, Hyunsoo (International Journal of Population Data Science, 2017)
ABSTRACT Background Data linkage is a method to form a complete data that can provide more abundant information by combining a plurality of different data files. In this study, we construct the matched data combined with Korea Welfare Panel Survey and National Survey of Tax and Benefit by using statistical matching methodology. We aim to provide the empirical and advisable evidence for tax and welfare policy by analyzing about the welfare attitude in accordance with the welfare status of taxpayer or welfare recipient using matched data. Results According to the analysis results, people with dual status of taxpayer above the tax break-even point and welfare recipient due to recent enlargement of welfare programs are relatively more positive about the expansion of the universal welfare than taxpayers who never receive welfare benefit. Also, in the group with dual status, the recognition that the current tax burden of middle class is low is relatively higher and the negative thinking about the need to increase tax burden for the enlargement of the universal welfare programs is relatively lower than the group who pay tax but never receive welfare benefit.